2014
DOI: 10.1590/s0102-05362014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen accumulation and monitoring by strawberry stock plants for runner tips production

Abstract: The composition and concentration of the nutrient solution can affect growth of strawberry stock plants and runner tips production. The aim of this research was to determine runner tips production and nitrogen (N) accumulation by strawberry stock plants grown under five N concentrations in the nutrient solution and its relationships with chlorophyll meter readings. From September 2010 to March 2011, strawberry stock plants of cultivar Oso Grande and Camino Real were grown on sand polyethylene bags. Nitrogen wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(1 reference statement)
0
2
0
1
Order By: Relevance
“…In hydroponic growing system using sand as substrate, it was shown by Andriolo et al (2011) that increasing nitrogen levels in the nutrient solution had resulted in decline in most vegetative growth parameters of strawberry plants. In another study, Andriolo et al (2014) found no differences in runner tips production between nitrogen levels in the nutrient solution from 5.0 to 15.0 m mol/L. Similarly, Janisch et al (2012) reported on the effects of nitrogen level in the nutrient solution applied to strawberry mother plants in soilless culture on their runner tips production in the greenhouse.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In hydroponic growing system using sand as substrate, it was shown by Andriolo et al (2011) that increasing nitrogen levels in the nutrient solution had resulted in decline in most vegetative growth parameters of strawberry plants. In another study, Andriolo et al (2014) found no differences in runner tips production between nitrogen levels in the nutrient solution from 5.0 to 15.0 m mol/L. Similarly, Janisch et al (2012) reported on the effects of nitrogen level in the nutrient solution applied to strawberry mother plants in soilless culture on their runner tips production in the greenhouse.…”
Section: Introductionmentioning
confidence: 90%
“…Bartczak et al (2007) did not find significant difference between two strawberry cultivars in runner production but the average ramet fresh weight was different. In hydroponic growing system, Andriolo et al, (2014) reported no difference between the two cvs. 'Camino Real' and 'Oso Grande' in runner production.…”
Section: Introductionmentioning
confidence: 92%
“…We concluded that increasing the concentration of the nutrient solution reduces the growth of strawberry stock plants and the production of runner tips and transplants is higher in the EC range between 0.8 and 1.1 dS/m. duvidosa e principalmente, atrasos na entrega aos produtores (Janisch et al, 2012;Andriolo et al, 2014). O cultivo sem solo e a produção de mudas com torrão permitem formação de mudas com alta qualidade, baixa infestação por patógenos e plantio na época adequada, proporcionando, assim, aumento na produção de frutos na entressafra (Giménez et al, 2008;Janisch et al, 2012) com maior lucro para os produtores.…”
Section: Yield Of Strawberry Runner Tips Under Different Electrical Cunclassified